2015
DOI: 10.1016/j.devcel.2014.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of β1 Integrin-Klf2-Mediated Angiogenesis by CCM Proteins

Abstract: Mechanotransduction pathways are activated in response to biophysical stimuli during the development or homeostasis of organs and tissues. In zebrafish, the blood-flow-sensitive transcription factor Klf2a promotes VEGF-dependent angiogenesis. However, the means by which the Klf2a mechanotransduction pathway is regulated to prevent continuous angiogenesis remain unknown. Here we report that the upregulation of klf2 mRNA causes enhanced egfl7 expression and angiogenesis signaling, which underlies cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
162
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(173 citation statements)
references
References 73 publications
(104 reference statements)
10
162
1
Order By: Relevance
“…However, this does not deny the possibility that human ECFC-derived vasculature connect to constitute the branches of mice vasculature to improve blood flow. However, integrin b 1 has been reported to have an independent angiogenesis-stimulating function, and one of the principle downstream effector molecules for integrin b 1 is vascular endothelial growth factor (VEGF) [15,16,39,40]. The excreted VEGF from exogenous ECFCs could stimulate new blood vessel formation, not only from exogenous human ECFCs, but also from endogenous mouse ECFCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this does not deny the possibility that human ECFC-derived vasculature connect to constitute the branches of mice vasculature to improve blood flow. However, integrin b 1 has been reported to have an independent angiogenesis-stimulating function, and one of the principle downstream effector molecules for integrin b 1 is vascular endothelial growth factor (VEGF) [15,16,39,40]. The excreted VEGF from exogenous ECFCs could stimulate new blood vessel formation, not only from exogenous human ECFCs, but also from endogenous mouse ECFCs.…”
Section: Discussionmentioning
confidence: 99%
“…We surmised that while circulating in the blood, integrin b 1 -expressing cells would naturally home to ischemic tissue, because it abundantly expresses extracellular matrix (ECM) proteins, the ligands for integrins [12][13][14]. In addition, integrin b 1 has been reported to have an independent angiogenesis stimulating function [15,16], which we expected could also result in beneficial effects on ischemic legs.…”
Section: Introductionmentioning
confidence: 99%
“…On a cautionary note, however, it should be noted that zebrafish klf2a mutants do not exhibit any obvious cardiovascular defects (Novodvorsky et al, 2015). This could be due to genetic redundancy with klf2b, which is also expressed at cardiac cushions (Renz et al, 2015), or to some other genetic compensatory mechanism. Additional experiments are required to resolve this issue.…”
Section: Mechanosensitive Pathways Within the Endocardiummentioning
confidence: 99%
“…We then review the role of endocardial-myocardial signalling and the impact of blood flow during cardiac morphogenesis. We also highlight how dysregulated blood flow responses within the endocardium can have pathological consequences (Renz et al, 2015;Zhou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of the CCM3 gene have been linked to cerebral cavernous malformations -vascular abnormalities characterised by dilated leaky cerebral lesions that can lead to brain haemorrhage (Draheim et al, 2014). The exact mechanism by which cerebral cavernous malformations arise is still subject to debate, with deregulation of several signalling pathways such as RHO (Richardson et al, 2013;Stockton et al, 2010;Borikova et al, 2010;Whitehead et al, 2009), TGFβ (Maddaluno et al, 2013), β-catenin (Bravi et al, 2015) and MEKK3-KLF2 or MEKK3-KLF4 (Cuttano et al, 2016;Zhou et al, 2016;Renz et al, 2015) having been demonstrated to be involved in development and progression of the disease. Crucially, loss of the CCM3 interaction with GCKIII kinases seems to be the crucial feature of all disease-associated CCM3 mutations (Fidalgo et al, 2010).…”
Section: E-2mentioning
confidence: 99%